The effectiveness of promotional mix towards Adabi's products among consumers in Rawang, Selangor / Nor Shamimi Abu Bakar (Faculty of Business Management, 2006)
Report on a study of the effectiveness of promotional mix towards Adabi's products in Rawang, Selangor. The study comprised 52 customers. A frequency table was conducted to determine which promotional mix that gives a big impact and most effectiveness to Adabi. Correlation was conducted to determine the correlation promotional effectiveness and promotional mix. Findings of this study showed that advertising has given a big impact to Adabi and it is the most effectiveness of promotional mix. Public relations has strong relationship with promotional effectiveness. Conclusion with a discussion of the recommendation to increase sales.